Предмет: Математика,
автор: Аноним
Упростите выражение:
а)-0,6а×0,75b×(-c)
б)-(2a-3)+(4a-2)
в)4(1,25x-0,9y)-3x+4,6y
Ответы
Автор ответа:
0
а)-0,6а×0,75b×(-c) = -0,45ab×(-c) = 0,45abc.
б)-(2a-3)+(4a-2) = -2a+3+4a-2 = 2a+1.
в)4(1,25x-0,9y)-3x+4,6y = 5x-3,6y-3x+4,6y = 2x+y.
б)-(2a-3)+(4a-2) = -2a+3+4a-2 = 2a+1.
в)4(1,25x-0,9y)-3x+4,6y = 5x-3,6y-3x+4,6y = 2x+y.
Похожие вопросы
Предмет: Українська мова,
автор: clevervladik
Предмет: Литература,
автор: anzhelal58
Предмет: Математика,
автор: BronyPony
Предмет: Алгебра,
автор: Frolova13